The Behaviour Of Dental And Oral Health And Risk Of Caries In The Prolanis Group Of Klinik Pratama Firdaus Yogyakarta - Afina Hasnasari Heningtyas; Annisa Dian Puspita; Afryla Femillian (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
Background: Systemic diseases such as diabetes mellitus and hypertension can be associated and provide clinical manifestations in the oral cavity. These manifestations can certainly impact and feel uncomfortable and can reduce the function of the patient's oral cavity. Purpose: This study aims to describe the level of knowledge, attitudes, and oral health measures and the risk of caries in patients with diabetes mellitus and hypertension in the Prolanis group. Methods: This study was a descriptive observational study with a cross-sectional study design. The questionnaire used was a knowledge, attitude, and action questionnaire and a risk assessment caries form. Results: Of the 46 respondents, half (56.5%) had hypertension, half (69.6%) were female, and half (58.7%) were in the age range of 60-74 years. 67.4% of respondents have moderate knowledge, 60.9% have a good attitude, and 87% have adequate oral and dental health measures. More than half of the respondents (71.7%) fall into the high caries risk category. Conclusion: Most of the respondents' knowledge level is in the medium category, the attitude level is in a positive category, and the activity level is in the moderate category. The caries risk category of respondents is in the high-risk category.